2019
DOI: 10.1038/s41386-019-0444-2
|View full text |Cite
|
Sign up to set email alerts
|

Arousal and sleep circuits

Abstract: The principal neurons of the arousal and sleep circuits are comprised by glutamate and GABA neurons, which are distributed within the reticular core of the brain and, through local and distant projections and interactions, regulate cortical activity and behavior across wake-sleep states. These are in turn modulated by the neuromodulatory systems that are comprised by acetylcholine, noradrenaline, dopamine, serotonin, histamine, orexin (hypocretin), and melanin-concentrating hormone (MCH) neurons. Glutamate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(128 citation statements)
references
References 198 publications
(232 reference statements)
5
109
0
Order By: Relevance
“…Neurons that comprise arousal-promoting nuclei can either act as local interneurons or project broadly to influence the activity of multiple brain regions, including the neocortex 21 . To assess which of these categories mWAKE DMH neurons belong to, we injected an AAV vector expressing Cre-dependent eGFP (AAV-FLEX-eGFP) into the DMH of mWAKE (Cre/+) mice and imaged the GFP + projections (Fig.…”
Section: Mwake Defines a Novel Clock-regulated Arousal Circuit In Thementioning
confidence: 99%
“…Neurons that comprise arousal-promoting nuclei can either act as local interneurons or project broadly to influence the activity of multiple brain regions, including the neocortex 21 . To assess which of these categories mWAKE DMH neurons belong to, we injected an AAV vector expressing Cre-dependent eGFP (AAV-FLEX-eGFP) into the DMH of mWAKE (Cre/+) mice and imaged the GFP + projections (Fig.…”
Section: Mwake Defines a Novel Clock-regulated Arousal Circuit In Thementioning
confidence: 99%
“…By the middle of the last century, it was increasingly clear that structures in the brainstem have a substantial role in the modulation of cortical states (Jones, 2008(Jones, , 2020. Early experiments of Moruzzi and Magoun (1949) showed that electrical stimulation of the brainstem i.e., the reticular activating system, and other subcortical structures could abolish cortical synchrony in the EEG, replacing it with low amplitude fast activity.…”
Section: Neuromodulation and The Hypothalamusmentioning
confidence: 99%
“…We now understand that many of the deep structures in the brainstem, midbrain, and hypothalamus are part of a large, interconnected neuromodulatory network that acts both directly and indirectly on the cortex to change brain states ( Figure 1B). Collectively, these structures, which include the locus coeruleus, pedunculopontine nucleus, tuberomammillary nucleus, and others constitute the reticular activating system (reviewed in Jones, 2008Jones, , 2020. Each structure is associated with a particular neuromodulatory transmitter, and stimulation of each of these structures can induce cortical state changes.…”
Section: Neuromodulation and The Hypothalamusmentioning
confidence: 99%
“…Furthermore, source distributions might change drastically during recording time. For instance, dominant sources alter drastically during the transition from wake state to sleep (Steriade, 2003) and during sleep cycles (Pace-Schott and Hobson, 2002; Steriade, 2003; Dang-Vu et al, 2010; Brown et al, 2012; Jones, 2019). Even the much longer circadian rhythm (Dijk and Czeisler, 1995; Pace-Schott and Hobson, 2002; Brown et al, 2012) is regulated by specific neuronal circuits.…”
Section: Introductionmentioning
confidence: 99%